(untitled) (Iranian Journal of Kidney Diseases, 2018)
Introduction. Chronic kidney disease (CKD) is frequent amongst human immunodeficiency virus (HIV)-positive patients, and screening is not routinely performed in Sub-Saharan Africa due to resource constraints. We aimed to determine the prevalence of CKD and associated factors in HIV-infected patients in Cameroon. Materials and Methods. A cross-sectional study in Northern Cameroon included HIV-positive patients who attended the HIV clinic. Patients with an estimated glomerular filtration rate less than 60 mL/min/1.73 m² or urinary abnormalities underwent a second measurement 3 months later. Glomerular filtration rate was estimated using the 4-variable Modification of Diet in Renal Disease (MDRD) and the Chronic Kidney Disease Epidemiology Collaboration (CKD-EPI) equations. Logistic regression was used to identify factors associated with CKD. Results. We included 709 participants. The median CD4 count was 219 cells/mL. Proteinuria accounted for 34.4%; leukocyturia, 6.9%; and hematuria, 6.1%. Prevalence of CKD was 44.4% (CKD-EPI) and 47.2% (MDRD). Stages 3 to 5 of CKD were documented in 11.6% using the CKD-EPI and 7.5% using the MDRD. Factors associated with CKD were an age greater than 35 years (odds ratio [OR], 104; 95% confidence interval [CI], 1.02 to 1.06), longer duration of HIV (OR, 2.60; 95% CI, 1.53 to 3.95), history of hepatitis B (OR, 3.04; 95% CI, 1.08 to 8.54), and CD4 cells less than 200 cells/mL (OR, 3.64; 95% CI, 2.55 to 5.21). Conclusions. The prevalence of CKD is high among HIV patients in Cameroon. There is a need of implementing measures to encourage early detection of kidney disease in these patients.